The Use of Artificial Intelligence in the Management of Neurodegenerative Disorders; Focus on Alzheimer’s Disease: Artificial Intelligence and Alzheimer’s Disease - Ghasempour Dabbaghi, Khazar; Khosravirad, Zahra; Jamalnia, Sheida; GhorbaniNia, Rahil; Mahmoudikohani, Fatemeh; Zakeri, Habib; Khastehband, Solmaz (Galen Medical Journal, 2023)
Recent advances in artificial intelligence (AI) have shown great promise in the diagnosis, prediction, treatment plans, and monitoring the progression of neurodegenerative disorders. AI algorithms can analyze large amounts of data from various sources, including medical images, quantifiable proteins in urine, blood, and cerebrospinal fluid (CSF), genetic information, clinical records, Electroencephalography (EEG) signals, driving behaviors, etc. Alzheimer’s disease as one of the most common neurodegenerative disorders. This study specifically explores the possible application of AI in the diagnosis, prediction, monitoring of disease progression, classifying, finding new biomarkers and drugs, and personalizing treatment plans of AD.